2018
DOI: 10.1364/ao.57.001043
|View full text |Cite
|
Sign up to set email alerts
|

Principal frequency component analysis based on modulate chopper technique used in diffuse reflectance spectroscopy measurement

Abstract: Diffuse reflectance spectroscopy (DRS) is significantly affected from the interference of the ambient light and dark current of the instrument. Optical choppers, together with lock-in/synchronous amplification, can overcome these interferences. However, in spectral measurement, the sampling rate of the spectrometer is different from the Δ-pulse sampling, which is not high enough because of the integration time. In addition, the energy distribution is not perfectly concentrated as expected in modulate chopper t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, disks choppers with windows with linear margins (what we called "classical" choppers) have a limited possibility of generating different profiles of laser impulses, although we have demonstrated that, using certain relationships between its geometrical parameters and those of the laser beam, one can obtain a range of such profiles [14,15], even for the simpler case (from an analytical point of view) of top-hat incident laser beams. Therefore, we have first proposed and patented [17] a configuration of chopper disk with non-linear margins, outward or inward oriented.…”
Section: Choppers With Shafts Vs Choppers With Disksmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, disks choppers with windows with linear margins (what we called "classical" choppers) have a limited possibility of generating different profiles of laser impulses, although we have demonstrated that, using certain relationships between its geometrical parameters and those of the laser beam, one can obtain a range of such profiles [14,15], even for the simpler case (from an analytical point of view) of top-hat incident laser beams. Therefore, we have first proposed and patented [17] a configuration of chopper disk with non-linear margins, outward or inward oriented.…”
Section: Choppers With Shafts Vs Choppers With Disksmentioning
confidence: 99%
“…Therefore, the transmission functions of the latter can be obtained as particular cases, when ρ → ∞ (thus, the windows margins would become linear). We have named these novel devices "eclipse" choppers, because of the way the obscuration of the section of the beam in the plane of the disk occurs, similarly to a planetary eclipse [15][16][17], and somehow similar to the way vignetting is produced in optical systems [35].…”
Section: Choppers With Shafts Vs Choppers With Disksmentioning
confidence: 99%
See 2 more Smart Citations
“…Song et al. 38 improved the S/N by reconstructing the signal with the fundamental frequency coefficient, while eliminating the background light interference. The spectrum was collected by short-time multiple sampling and obtained multiple frequency information.…”
Section: Spectral Data Acquisition Preprocessing and Modelingmentioning
confidence: 99%